2012
DOI: 10.2147/ccid.s36102
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol-procyanidin blend: nutraceutical and antiaging efficacy evaluated in a placebo-controlled, double-blind study

Abstract: BackgroundSkin is constantly exposed to pro-oxidant environmental stress from several sources, including air pollutants, ultraviolet solar light, and chemical oxidants. Reactive oxygen species have been implicated in age-related skin disorders. Dietary bioactive antioxidant compounds, such as polyphenols, have beneficial effects on skin health. The advantage of a nutritional administration route is that blood delivers nutraceutical bioactive compounds continuously to all skin compartments, ie, the epidermis, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…[304] wanted to evaluate the topical and systemic effects of a grape supplement containing 8 mg resveratrol and procyanidins on age-related alterations to the skin, the skin antioxidant pool, and systemic oxidative stress levels. An instrumental study was performed in 50 subjects (placebo, n=25, and treatment, n=25) with clinical signs of skin aging (wrinkles, dull complexion, brown spots) to identify clinical features induced by chronoaging or photoaging.…”
Section: Human Intervention Studiesmentioning
confidence: 99%
“…[304] wanted to evaluate the topical and systemic effects of a grape supplement containing 8 mg resveratrol and procyanidins on age-related alterations to the skin, the skin antioxidant pool, and systemic oxidative stress levels. An instrumental study was performed in 50 subjects (placebo, n=25, and treatment, n=25) with clinical signs of skin aging (wrinkles, dull complexion, brown spots) to identify clinical features induced by chronoaging or photoaging.…”
Section: Human Intervention Studiesmentioning
confidence: 99%
“…The investigators have reported that 4 weeks of resveratrol treatment, signifi cantly reduced triglyceride concentration and increased antioxidant status [ 4 ]. In another study resveratrol was evaluated against systemic oxidative stress, which revealed that it signifi cantly increases antioxidant properties [ 6 ]. Similarly, high level of resveratrol is shown to inhibit CYPs and interact with transporters which modify the CYPs-mediated metabolism [ 72 ].…”
Section: Resveratrol: Clinical Studiesmentioning
confidence: 99%
“…Also, it is potentially useful for the management of diabetic ulcers, [ 84 ] to treat comedonal and in fl ammatory acne, to improve skin damaged by UV exposure and to promote healing in herpes simplex virus 1 infection in mice [85][86][87] . Recently, a double blind, placebo controlled study has shown that supplementation with a speci fi c grape extract containing 8 mg of resveratrol, is effective in reducing skin wrinkling and oxidative damage [ 88 ] .…”
Section: Resveratrolmentioning
confidence: 99%